Hypoxia reconstructed colorectal tumor microenvironment weakening anti-tumor immunity: construction of a new prognosis predicting model through transcriptome analysis - Zhang, Ruizhi; Gao, Yisong; Li, Chong; Tao, Ruikang; Mao, Gan; Song, Tianyu; Nie, Wenxiang; Liu, Suao; Tao, Kaixiong; Li, Wei (Frontiers in Immunology, 2024)
BackgroundHypoxia in the tumor microenvironment (TME) plays a pivotal role in the progression and prognosis of colorectal cancer (CRC). However, effective methods for assessing TME hypoxia remain lacking. This study aims to develop a novel hypoxia-related prognostic score (HPS) based on hypoxia-associated genes to improve CRC prognostication and inform treatment strategies.MethodsTranscriptomic data from CRC patients were analyzed using Lasso regression to identify hypoxia-associated genes with the strongest prognostic significance. The identified genes were validated in vitro by assessing their expression under normoxic and hypoxic conditions in normal intestinal epithelial cells and CRC tumor cell lines. Functional relevance was explored through differential gene expression analysis, Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses, and protein-protein interaction (PPI) network construction. The association of HPS with extracellular matrix (ECM) composition, immune cell infiltration, and immune suppression was also investigated.ResultsSeven hypoxia-associated signature genes were identified, each demonstrating a strong correlation with CRC prognosis. The hypoxia-related prognostic score (HPS), derived from these genes, was significantly linked to changes in the TME. Specifically, HPS values were associated with alterations in ECM composition and distinct immune cell infiltration patterns. Higher HPS values corresponded to increased infiltration of immune-suppressive cells and reduced presence of anti-tumor immune cells. This imbalance promoted an immune-suppressive TME, facilitating tumor progression and immune evasion.ConclusionsThe hypoxia-related prognostic score (HPS) captures the regulatory influence of TME hypoxia on immune responses, offering valuable insights into its role in tumor progression. HPS holds promise as a prognostic tool and a guide for developing personalized treatment strategies in CRC.